Buckling behaviours of functionally graded polymeric thin-walled hemispherical shells - Uysal, Mine U. (TECHNO-PRESS, 2016)
This paper investigates the static buckling behaviours of Functionally Gradient Polymeric Material (FGPM) shells in the form of hemispherical segment. A new FGPM model based on experimental was considered to investigate the buckling problem of thin-walled spherical shells loaded by the external pressure. The spherical shells were formed by FGPM which was produced adding the two types of graphite powders into epoxy resin. The graphite powders were added to the epoxy resin as volume of 3, 6, 9, and 12%. Halpin-Tsai and Paul models were used to determine the elastic moduli of the parts of FGPM. The detailed static buckling analyses were performed by using finite element method. The influences of the types and volume of graphite powders on the buckling behaviour of the FGPM structures were investigated. The buckling loads of hemispherical FGPM shells based on Halpin-Tsai and Paul models were compared with those determined from the analytical solution of non-graphite condition existing for homogeneous material model. The comparisons between these material models showed that Paul model was overestimated. Besides, the critical buckling loads were predicted. The higher critical buckling loads were estimated for the PV60/65 graphite powder due to the compatible of the PV60/65 graphite powder with resin.
Keywords: hemispherical thin shells; functionally graded polymeric materials (FGPMs); external pressure; static buckling; finite element analysis (FEA); SHALLOW SPHERICAL-SHELLS; DENSITY POLYETHYLENE COMPOSITES; SHEAR DEFORMATION-THEORY; CYLINDRICAL-SHELLS; EXTERNAL-PRESSURE; POSTBUCKLING BEHAVIOR; MEMBRANE ANALYSIS; FREE-VIBRATION; CYLINDERS; STABILITY; Construction & Building Technology; Engineering; Materials Science